A mortality cohort study among workers in a graphite electrode production plant in Italy. Issue 2 (22nd January 2004) - Merlo, D F; Garattini, S; Gelatti, U; Simonati, C; Covolo, L; Ceppi, M; Donato, F
Abstract : Background: Graphite electrode manufacturing workers are exposed to coal tar and its volatiles containing a variety of polycyclic aromatic hydrocarbons (PAH), silica and graphite dusts, and asbestos. Aims: To investigate mortality from cancer and other diseases among workers in a graphite electrode production plant in Italy. Methods: A total of 1291 males actively employed between 1 January 1950 and 31 December 1989 who had worked at the plant for at least one year were studied. The follow up extended from 1950 to 1997. Standardised mortality ratios (SMR) and their 95% confidence intervals (CI) were computed using mortality rates for the Italian and regional male population. Results: Excess mortality was observed for all causes (SMR 1.44, CI 1.32 to 1.56), all cancers (SMR 1.27, CI 1.07 to 1.50), liver cancer (SMR 4.19, CI 2.68 to 6.23), silicosis (SMR 66.39, CI 52.56 to 82.7), and cirrhosis and other chronic diseases of the liver (SMR 1.87, CI 1.31 to 2.59) in comparison with the national male population. When regional rates were used to calculate the number of expected deaths, SMRs remained higher for silicosis (SMR 57.32, 42.11 to 76.22), and liver cancer (SMR 2.57, 1.57 to 3.97). Mortality from silicosis was increased in workers hired at young ages (<25 years, SMR 81.79; 25–34 years, SMR 82.73), and in workers aged <45 at death (SMR 333.3, CI 159.8 to 613). Mortality from liver cancer increased threefold (SMR 3.11, CI 1.78 to 5.05) in workers with more than 10 years of employment at the plant during the manufacture of Karbate products. Conclusions: Results support the association between excess mortality from silicosis and occupational exposure to siliceous sands experienced during graphite electrode manufacturing. The observed excess mortality from liver cancer is compatible, to some extent, with exposures that may have occurred during the manufacture of phenolic and furfuryl resins treated products, although a role of lifestyle factors and viral infections cannot be excluded.